A review of recent developments for the in situ/operando characterization of nanoporous materials. Issue 16 (8th July 2022) - Petersen, Hilke; Weidenthaler, Claudia
Abstract : This review article summarizes some of the recent developments in the field of nanoporous materials characterization. Abstract : This is a review on up-to-date in situ / operando methods for a comprehensive characterization of nanoporous materials. The group of nanoporous materials is constantly growing, and with it, the variety of possible applications. Nanoporous materials include, among others, porous carbon materials, mesoporous silica, mesoporous transition metal oxides, zeolites, metal–organic frameworks (MOFs), or polymers. They are used as adsorbents, for gas storage, as catalysts, or for electrochemical applications to name just a few technical applications. Characterization of these materials has evolved from pure ex situ examination to increasingly complex in situ or operando methods. Monitoring nanoporous materials under reaction conditions allows for establishing structure–property relationships. This enables nanoporous materials to be adapted and optimized for specific processes. Recent developments on well-established but also exciting emerging methods for future applications will be discussed. The examples include in situ powder diffraction, total and small angle scattering, environmental electron microscopy, coupled with focused ion beam cutting, or X-ray tomography. This article will provide a useful reference to practitioners for in situ / operando characterization of nanoporous materials.